Methodology for Fabrication-Tolerant Planar Directional Couplers - Choon Kong Lai; Yile Zhong; Wu Yi Chong; Duk-Yong Choi; Harith Ahmad; Stephen Madden (IEEE Photonics Journal, 2022)
A new methodology for realizing fabrication-tolerant planar directional couplers is proposed and experimentally demonstrated. Performance of power splitting and WDM couplers can be made highly tolerant to typical process errors when an appropriate center-to-center spacing is chosen due to changes in the mode area compensating waveguide edge to edge variation along a very specific design locus. Using this approach, 2–3% index contrast waveguide couplers were fabricated and tested, demonstrating the predicted improved fabrication tolerances. High index contrast silicon-on-insulator systems are also shown to exhibit the same mechanism. The high fabrication tolerance demonstrated is of particular importance for vertically stacked hybrid integration of different materials platforms, where achieving tight critical dimension control over significant physical topology is problematic. Additionally the method will be of utility in circumstances where tight tolerances are required on coupling ratios such as coupled resonator filter devices etc.